Anthropometry Application for Flexible Chair College - Andarmadi Jati Abdhi Wasesa; Muhamad Abdul Jumali (UNIPA PRESS, 2021)
Anthropometry is a part of ergonomics that specifically studies body size which includes linear dimensions, as well as content, also includes areas of size, strength, speed, other aspects of body movement.Chairs are furniture that functions as seats, with the demands of the public for the design of chairs, many innovations have sprung up for the manufacture of chairs, the comfort factor is the most served in the process of making chairs, one of which is the lecture chair.The research subjects in this study were undergraduate students at a tertiary institution in East Java with male and female sex, with an age range of 18-25 years. As a result, for Hips Width The size of the seat width used is 36 cm (95th percentile) so that large people can fit when occupying a chair, for Back Height The height of the chair is 57 cm (5th percentile) so that people with small body postures can sit comfortably without difficulty, for Knee Length The length of the knee is 61 cm (95th percentile).